Pengaruh Kualitas Pelayanan Pendafataran Rawat Jalan Terhadap Kepuasan Pasien BPJS Di Rumah Sakit Umum Avisena Cimahi - Soejoto, Nina; Ariani, Nurul Dwi; Aulia, Dede Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This studyaims to determine the effect of the quality of outpatient registration services on BPJS patient satisfaction at Rumah Sakit Umum Avisena Cimahi. The research method used by the author is a descriptive research method with a quantitative approach, data analysis techniques: validity test, reliability test, Spearman rank correlation test and coefficient of determination test. Data collection techniques used were observation, questionnaires and literature study with the research subjects werepatienst or their families who were waiting for the outpatient registration queue at Rumah Sakit Umum Avisena Cimahi. The result showed that the effect of the quality of outpatient registration services on BPJS patient satisfaction, namely the large influence of the service quality variable on patient satisfaction was 61,1% and the rest was influenced by other factors of 38,9%. The problems found from the results of the study are (1) registration officiers are only 1-2 people at 06.00 – 08.00 (2) The Average outpatient registration service for each patient is 3-5 minutes (3) There is no special place for registration of inpatient and emergency rooms. The author gives suggenstions from these problems, namely (1) Registration officer at 06.00 – 08.00 to 3 people (2) To disseminate an easy way to register online through the RSU Avisena application (3) To hold a special place for registration of inpatient and emergency rooms.